PENGARUH PENGGUNAAN MODEL MIND MAPPING TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV - Anida Fiqrunisa; Suhardi Marli; Asmayani Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to analyze the effect of the use of mind mapping models on thematic learning of fourth grade students at SDN 10 East Pontianak. The method used is the experimental method, a form of research Quasi Experimental Design, with the type of Non-Equivalent Control Group Design. . The research sample consisted of class IV A as a control class and IV B as an experimental class. The population in this research is all fourth grade students consisting of 54 students. The data collection tool used was a from multiple choice questions with 45 questions. Based on data analysis, the average post-test results of the experimental class were 79 while the average post-test results of the control class were 72.29. The results of the t-test are obtained tcount of  2,138 and ttable α = 5% (dk = 25 + 22 - 2 = 45 ) of 1.669. Because tcount (2.138)> ttable (1.669)  Ha is accepted. The effect size obtained is 0.4486 (medium criterion) is obtained. This means that the use of the Mind Mapping model on the results of thematic learning has a good influence on the learning outcomes of fourth grade students at SDN 10 East Pontianak. Keywords: Mind Mapping Models, Thematic Learning, Learning Outcomes